Comparison of skin autofluorescence, a marker of tissue advanced glycation end‐products in peritoneal dialysis patients using standard and biocompatible glucose containing peritoneal dialysates. Issue 8 (2nd May 2019) - Vongsanim, Surachet; Fan, Stanley; Davenport, Andrew
ABSTRACT: Background: Heat sterilization of peritoneal dialysis (PD) dialysates leads to the generation of advanced glycation products (AGE), which can then deposit in the skin and be measured by skin autofluorescence (SAF). Newer biocompatible dual chamber dialysates contain less AGE. We wished to determine whether the use of these newer dialysates resulted in lower SAF. Methods: Skin autofluorescence was measured using the AGE reader, which directs ultraviolet light, intensity range 300–420 nm (peak 370 nm) in patients established on PD for >3 months using glucose containing dialysates. Results: We screened 196 consecutive patients, and measured SAF in 150; 86 (57.3%) male, median age 62 (53–71) years, median duration of PD treatment 17 (8.6–34.3) months. The median SAF was 3.48 (2.92–4.26) AU. The median SAF in the 57 (38%) patients prescribed biocompatible dual chamber bag dialysates was 3.39 (2.69–3.98) versus 3.5 (3.05–4.54) for those using standard dialysates ( P  = 0.044). Although prescription of biocompatible fluids was associated with SAF on univariate analysis, but not on multivariable testing, SAF was independently associated with Stoke–Davies co‐morbidity grade ( β 0.045, 95% confidence limits (CL) 0.015–0.075, P  = 0.002), log duration of PD therapy ( β 0.051, CL 0.001–0.101, P  = 0.045), white ethnicity ( β 0.066, CL 0.028–0.104, P  = 0.001), and negatively with serum albumin ( β −0.006, CL −0.008 to −0.004, P  = 0.014). Conclusion: Although SAF was lower in PD patients prescribed biocompatible dual chamber dialysates, on multivariable testing these dialysates were not independently associated with SAF. Other factors than PD fluid AGE content appear more important in determining SAF. SUMMARY AT A GLANCE: The authors looked at the effect of newer biocompatible peritoneal dialysis solutions on the deposition of advanced glycation products in the skin by autofluorescence and found mixed results.